Effect of first ball possession on partial and final scores in 2003, 2005, and 2007 water polo world championships - Argudo, F. M.; Arias, J. L.; Ruiz, E.; Alonso, J. E. (Perceptual and Motor Skills, 2011)
The purpose was to analyze the influence of winning the first ball possession on the partial and final score in male and female water polo. The 288 matches disputed by the teams participating in the 2003, 2005, and 2007 Water Polo World Championship were recorded. The results reflect statistically significant differences for the influence of gaining the first ball possession on the partial and final scoreboard of each period and for the influence between the total number of first possessions obtained and the final result